Oxygen-induced impairment in arterial function is corrected by slow breathing in patients with type 1 diabetes - Luciano Bernardi (Nature Portfolio, 2017)
Abstract Hyperoxia and slow breathing acutely improve autonomic function in type-1 diabetes. However, their effects on arterial function may reveal different mechanisms, perhaps potentially useful. To test the effects of oxygen and slow breathing we measured arterial function (augmentation index, pulse wave velocity), baroreflex sensitivity (BRS) and oxygen saturation (SAT), during spontaneous and slow breathing (6 breaths/min), in normoxia and hyperoxia (5 L/min oxygen) in 91 type-1 diabetic and 40 age-matched control participants. During normoxic spontaneous breathing diabetic subjects had lower BRS and SAT, and worse arterial function. Hyperoxia and slow breathing increased BRS and SAT. Hyperoxia increased blood pressure and worsened arterial function. Slow breathing improved arterial function and diastolic blood pressure. Combined administration prevented the hyperoxia-induced arterial pressure and function worsening. Control subjects showed a similar pattern, but with lesser or no statistical significance. Oxygen-driven autonomic improvement could depend on transient arterial stiffening and hypertension (well-known irritative effect of free-radicals on endothelium), inducing reflex increase in BRS. Slow breathing-induced improvement in BRS may result from improved SAT, reduced sympathetic activity and improved vascular function, and/or parasympathetic-driven antioxidant effect. Lower oxidative stress could explain blunted effects in controls. Slow breathing could be a simple beneficial intervention in diabetes.